Business and human rights: from principles to practice - Baumann-Pauly, Dorothée; Nolan, Justine (Routledge, 2016)
The relationship of human rights to business -- Regulatory framework and guiding principles -- Business and human rights : implementation challenges -- Defining and implementing human rights standards industry by industry -- Key constituents that drive the implementation of business and human rights -- Accountability and remedy -- Global rules, private actors : future challenges for business and human rights